PRINCIPLES OF EFFECTIVE IP ENFORCEMENT IN CYBERSPACE: LESSONS FROM UKRAINE AND INTERNATIONAL PRACTICE - Filinovych, Valeriia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: this paper is devoted to the study and analysis of the fundamental legal principles that underlie the protection and enforcement of intellectual property rights in cyberspace. The research focuses on identifying common approaches in Ukrainian legislation and international practice, particularly in the United States, Australia, and China, and on developing proposals for improving the regulatory framework for intellectual property enforcement in Ukraine. The methodological basis of the study includes general scientific methods (analysis, synthesis, deduction), comparative legal analysis, as well as formal-legal and systemic-structural methods. Results: the research reveals that a principle-based approach to IP regulation provides a stable foundation for effective enforcement in the digital environment. The author systematizes doctrinal views and international norms, offering a detailed overview of legal principles such as the rule of law, protection of ownership, balance of interests, good faith, national treatment, and minimum standards. The study emphasizes the need to harmonize national and international standards to ensure predictability, legal certainty, and stronger protection of IPRs online. Recommendations are provided for implementing these principles in Ukraine’s legal and policy frameworks. Discussion: the internet’s borderless nature exacerbates the challenges of enforcing IPRs in cyberspace, inconsistent national regulations, and the growing sophistication of infringement methods. Addressing these issues requires practical enforcement tools and a shared commitment to fundamental legal principles at both the national and international levels. Ukraine’s alignment with global best practices in principle-based IP governance will foster innovation, support economic development, and contribute to stronger legal protection in the digital domain.